Macrophage activation and polarization in post-infarction cardiac remodeling - Gombozhapova, Aleksandra; Kzhyshkowska, Julia (Journal of biomedical science, 2017)
Adverse cardiac remodeling leads to impaired ventricular function and heart failure, remaining a major cause of mortality and morbidity in patients with acute myocardial infarction. It have been shown that, even if all the recommended therapies for ST-segment elevation myocardial infarction are performed, one third of patients undergoes progressive cardiac remodeling that represents morphological basis for following heart failure. The need to extend our knowledge about factors leading to different clinical scenarios of myocardial infarction and following complications has resulted in a research of immuno-inflammatory pathways and molecular activities as the basis for post-infarction remodeling. Recently, macrophages (cells of the innate immune system) have become a subject of scientific interest under both normal and pathological conditions. Macrophages, besides their role in host protection and tissue homeostasis, play an important role in pathophysiological processes induced by myocardial infarction. In this article we summarize data about the function of monocytes and macrophages plasticity in myocardial infarction and outline potential role of these cells as effective targets to control processes of inflammation, cardiac remodeling and healing following acute coronary event.
Gesehen am 02.10.2018